PENGARUH KERAGAMAN PRODUK, TATA LETAK PRODUK DAN SUASANA TOKO TERHADAP MINAT BELI ULANG - Lili Salfina, Lili Salfina; Fernando, Reynaldi (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
Abstract The   clothing   business   in   Indonesia   is   growing   following   the   current   of odernization. More and more business people in the field of fashion will result in increasingly  fierce  competition.   This  competition   makes   business  people  formulate strategies so that the business they are involved in can survive. The Rasky Fashion located in  the  Balai  Baru  area  faces  this  situation  because  of  its  location  or  proximity  to competitors who offer similar products. In this case, Rasky Fashion also very concerned about the level of sales, which does not increase significantly every year. This study aims to determine the effect of product diversity, product layout, store atmosphere on partial and simultaneous repurchase interest. This type of research is quantitative with multiple linear regression analysis method using primary data, data collection methods are carried out by interviewing  and  distributing  questionnaires.  The  population  of  this  research  is  the customer of Rasky Fashion, the determination of the number of samples using the Roscoe technique, obtained as many as 40 respondents with the withdrawal using the purposive sampling  method.  The  results  showed  that  product  diversity, product  layout  and  store atmosphere had a significant effect on repurchase interest at Rasky Fashion partially and simultaneously. The regression is Y = 5,435 + 0,369 X1 + 0,261 X2 + 0,302 X3 and the Adjusted R Square value is 0.683, meaning that the independent variable is able to explain the dependent variable by 68.3% while the remaining 31.7% is explained by other variables not examined in this study.